1991
DOI: 10.1523/jneurosci.11-07-02032.1991
|View full text |Cite
|
Sign up to set email alerts
|

Social status in pairs of male squirrel monkeys determines the behavioral response to central oxytocin administration

Abstract: Oxytocin, when administered centrally, has been associated with the modulation of various social initiatives including maternal and sexual behaviors. The nature of these effects depends on gonadal hormone status. In the present experiments, we investigated the effects of centrally administered oxytocin on the behavior of pair-housed male squirrel monkeys during interactions with a familiar female monkey. Pairs of male squirrel monkeys established reliable and persistent dominance relationships with dominant ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(71 citation statements)
references
References 37 publications
2
67
0
1
Order By: Relevance
“…A review of some of the evidence for neurochemical control of vocalizations in anxiety-provoking circumstances has been presented by Newman [72]. In addition, the neuropeptides vasopressin (AVP) and oxytocin (OT) have attracted a lot of interest, due to the evidence that they are involved in regulating social attachment behavior in rodents and non-human primates [39,41,42,49,70,92,120,121].…”
Section: Neurochemical Control Of Cryingmentioning
confidence: 99%
“…A review of some of the evidence for neurochemical control of vocalizations in anxiety-provoking circumstances has been presented by Newman [72]. In addition, the neuropeptides vasopressin (AVP) and oxytocin (OT) have attracted a lot of interest, due to the evidence that they are involved in regulating social attachment behavior in rodents and non-human primates [39,41,42,49,70,92,120,121].…”
Section: Neurochemical Control Of Cryingmentioning
confidence: 99%
“…The magnocellular OT and AVP cells project to the posterior lobe of the pituitary, while the parvocellular division projects to the AP via the median eminence. OT, which is found only in mammals, is associated with reproductive and maternal behaviors, and is also implicated in a variety of social behaviors (Hughes et al, 1987;Insel, 1992;Winslow and Insel, 1991). It is specifically involved in the initiation of parturition and milk ejection, and is itself a stimulator of PRL secretion (see below) (Samson et al, 1986).…”
Section: Hypothalamusmentioning
confidence: 99%
“…Peripheral and central oxytocin administration also inhibits extinction and this promotes perseverative behaviors (de Wied et al, 1993). Central administration of vasopressin results in increased aggression and self-directed behaviors in rodents (Brown and King, 1984;Winslow and Insel, 1991), which Insel et al (1999) has suggested may be related to the self-injurious behavior, often stereotyped, observed in children with autism. Although analogies between animal and human behavior must be viewed with caution, these studies suggest that oxytocin may play a role in repetitive behaviors, a core feature of autism.…”
Section: Introductionmentioning
confidence: 99%